ANALISIS PENGARUH SERVICE DELIVERY DAN DIGITALISASI TERHADAP CUSTOMER SATISFACTION PADA PT. ISS INDONESIA - Heni Susilowati; Siswanto Siswanto (LPPM Politeknik Pratama, 2021)
This study aims to determine the effect of service delivery and digitization on customer satisfaction at PT ISS Indonesia. The population in this study are consumers who use the services of PT ISS Indonesia for cleaning services, security services, pest control and other services. The sampling technique used non-probability sampling taken as many as 95 respondents. The data obtained through the questionnaire was quantified using a Likert scale of 1-5 with a choice rating of strongly agree to strongly disagree to be tested for validity and reliability. Data analysis method using Multiple Linear Regression. The results showed that partially and simultaneously service delivery and digitization variables had a positive effect on customer satisfaction